2017
DOI: 10.2298/jas1702115a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence of Nigerian and Indian pearl millet accessions based on agronomical and morphological traits

Abstract: The study assessed the genetic diversity of pearl millet accessions grown in Nigeria and India based on morpho-agronomic traits in order to identify genotypes with superior characters which could be utilized in breeding programmes. Twenty-four pearl millet accessions were grown and evaluated for agronomic and morphological traits during the dry and wet seasons of 2015-2016. Data collected on the accessions using standard descriptors were analysed statistically. IP22281 had the highest mean plant height (108.90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
7
4
0
Order By: Relevance
“…Variation in days to anthesis; 66.33 to 90.00 days for early variety and 106.00 to 129.33 days for late variety observed in this study corroborate with the earlier findings of60 days reported for early flowering accessions and 120 days for late flowering accessions in finger millet [22]. These values are higher than the values (ranged of 44 to 56 days) earlier reported Animasaun et al [23], and attributed the differences in anthesis time to photoperiodic sensitivity of the plant [23]. The variation in these results could be attributed to the difference in the response of plant to the environmental condition and the genetic nature of seeds.…”
Section: Discussionsupporting
confidence: 92%
“…Variation in days to anthesis; 66.33 to 90.00 days for early variety and 106.00 to 129.33 days for late variety observed in this study corroborate with the earlier findings of60 days reported for early flowering accessions and 120 days for late flowering accessions in finger millet [22]. These values are higher than the values (ranged of 44 to 56 days) earlier reported Animasaun et al [23], and attributed the differences in anthesis time to photoperiodic sensitivity of the plant [23]. The variation in these results could be attributed to the difference in the response of plant to the environmental condition and the genetic nature of seeds.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated the role of traits (specific to each PC) which contributed more towards genetic divergence in discriminating the genotypes of pearl millet. The present study was in agreement with the PCA traits analysis of Kumari et al, (2016), Animasaun et al, (2017), Radhika Ramya et al, (2017, Sangwan et al, (2019) in pearl millet. The Genotype-trait biplot based on two principal components were also generated to represent the two-dimensional view of eleven traits and different genotypes of pearl millet (Fig.…”
Section: Principle Component Analysissupporting
confidence: 93%
“…Genotypes from different source/origin falls under the same cluster, so grouping did not happened on the basis of origin or geographical location. These results are in agreement with the findings of Burson et al, (2015) and Animasaun et al, (2017) who observed that accessions of pearl millet did not necessarily assemble into the same cluster based on their geographical origins. Clustering of pearl millet accessions together regardless of their source supports the possibility of a common progenitor but separation by geographical or ecological isolation mechanisms (Jauhar, 1981).…”
Section: Cluster Analysissupporting
confidence: 93%
“…The diversity of individuals from Senegal was the lowest, whereas individuals of accessions from Nigeria recorded the highest level of diversity. The high level of genetic diversity of individuals of pearl millet accessions from Nigeria confirms reports by Animasaun et al (2017). The high level of genetic diversity of individuals of pearl millet accessions from Nigeria could be due to low level of human selection or outcrossing between cultivated Table 4.…”
Section: Discussionsupporting
confidence: 81%